Shoot multiplication, microtuber production and evaluation of antioxidant and cancer cell cytotoxicity activities of chlorophytum borivilianum Sant. & Fernandez - Ashraf, Mehdi Farshad (2012)
Chlorophytum borivilianum is an important medicinal plant. The tuberous roots possess immunomodulatory and adaptogenic properties, and are used to cure impotency, sterility and enhance male potency. The seeds have poor germination percentage (11-24%), low viability and long dormancy period. Considering Safed musli is an endangered species and the limited availability of planting materials, the use of tissue culture system could provide a rapid method for mass propagating the plant. In this study, young shoot buds of C. borivilianum were cultured on Murashige and Skoog (MS) medium containing BAP and Kn, both at 0, 8.88, 17.8 and 26.6 μM, either individually or in combination. Proliferated shoots were subcultured on fresh medium of the same constituents at 3 weeks interval. The combination of 8.88 μM BAP and 8.88 μM Kn was most suitable for shoot multiplication andongation of C. borivilianum. In vitro shoot tips of C. borivilianum were cultured for microtuber induction on MS solid medium containing different concentrations of 0, 315, 630, 950, 1265 and 1580 μM CCC combined with 30, 60 and 90 g l-1 of sucrose. The combination of 950 μM CCC and 60 g l-1 sucrose produced high number of microtubers with increased length. Upon using stationary liquid MS medium containing the different combinations of and sucrose as applied for solid medium, microtuber production was improved and the best combination was also in medium containing 950 μM CCC and 60 g l-1 sucrose. For optimization of microtuber production, comparison between solid, stationary and shake liquid cultures was carried out. Liquid culture with shaking at 80rpm resulted in more than 2.5 fold increase in microtuber production compared to solid culture. The study was extended using RITA system for scaling up of icrotuberization. Microtuberization was enhanced and hyperhydricity was eliminated using 15 min immersion time for every 60 min rest period. Substitution of the optimized liquid microtuberization medium (OLMM) containing 950 μM CCC and 60g l-1 sucrose with liquid hormone-free MS medium (MSO) on week 6 of culture was more economical for microtuberization than maintaining the culture throughout the 9 weeks on OLMM. Quantitation of total saponin showed a higher content in microtubers than in mother plant tubers. Analysis of antioxidant activity of crude and total saponin extracts from mother plant tubers of C. borivilianum indicated higher antioxidant activity of crude extract using DPPH and BCB assays, while higher chelating activity was shown by total saponin using FIC assay. Cytotoxicity evaluation of crude and total saponin extracts against MCF7, PC3 and HCT116 cancer cell lines using MTT cell viability assay indicated a higher cytotoxicity activity of the crude extract than the total saponin fraction on all cell lines, being most effectiveand selective on MCF7 human breast cancer cell line. In conclusion, shoot regeneration on solid medium, microtuber production on solid medium, in liquid medium and upscaling of microtuber production using a RITA system had been successfully established for C. orivilianum. The study also provided valuable information on the antioxidant and cytotoxicity activities of crude and total saponin extracts from tubers of C. borivilianum.